Blockade of the renin‐angiotensin‐aldosterone system in patients with arrhythmogenic right ventricular dysplasia: A double‐blind, multicenter, prospective, randomized, genotype‐driven study (BRAVE study). Issue 3 (25th March 2018) - Morel, Elodie; Manati, Ab Waheed; Nony, Patrice; Maucort‐Boulch, Delphine; Bessière, Francis; Cai, Xu; Besseyre des Horts, Timothee; Janin, Alexandre; Moreau, Adrien; Chevalier, Phillippe
Abstract : Arrhythmogenic right ventricular dysplasia (ARVD) is a rare cardiomyopathy characterized by the progressive replacement of cardiomyocytes by fatty and fibrous tissue in the right ventricle (RV). These infiltrations lead to cardiac electrical instability and ventricular arrhythmia. Current treatment for ARVD is empirical and essentially based on treatment of arrhythmia. Thus, there is no validated treatment that will prevent the deterioration of RV function in patients with ARVD. The aim of the BRAVE study is to evaluate the effect of ramipril, an angiotensin‐converting enzyme inhibitor, on ventricular myocardial remodeling and arrhythmia burden in patients with ARVD. Despite the fact that myocardial fibrosis is one of the structural hallmarks of ARVD, no study has tested an antifibrotic drug in ARVD patients. The trial is a double‐blind, parallel, multicenter, prospective, randomized, phase 4 drug study. Patients will be randomized into 2 groups, ramipril or placebo. The 120 patients (60 per group) will be enrolled by 26 centers in France. Patients will be followed up every 6 months for 3 years. The 2 co–primary endpoints are defined as the difference of telediastolic RV volume measured by magnetic resonance imaging between baseline and 3 years of follow‐up, and the change in arrhythmia burden during the 3 years of follow‐up. A decrease in RV and/or left ventricular deterioration and in arrhythmia burden are expected in ARVD patients treated with ramipril. This reduction will improve quality of life of patients and will reduce the number of hospitalizations and the risk of terminal heart failure.